2020
DOI: 10.1186/s42077-020-00078-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between magnesium sulphate and dexmedetomidine in controlled hypotension during functional endoscopic sinus surgery: a prospective randomized study

Abstract: Background Functional endoscopic sinus surgery (FESS) has been proposed as a selected treatment used in patients with chronic sinusitis that have not responded to medical therapy. Due to the nature of the location of endoscopic sinus surgery, even a small amount of bleeding can reduce the operative visibility. The aim of the work was to compare between dexmedetomidine and magnesium sulphate regarding their efficacy as a hypotensive agent in FESS in adult patients to obtain a bloodless surgical field. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…After induction, there was no statistically significant difference between the two groups regarding MAP at baseline before the loading dose; at induction, then at 15, 30 or 60 or 90 minutes; or after extubation; but after 30 minutes postoperatively, there was a statistically significant decrease in MAP among the (D group) 66.5 and 4.56 millimeters of mercury as compared to (M group) 73.11 and 4.74 millimeters of mercury (p=0.039) (14) .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…After induction, there was no statistically significant difference between the two groups regarding MAP at baseline before the loading dose; at induction, then at 15, 30 or 60 or 90 minutes; or after extubation; but after 30 minutes postoperatively, there was a statistically significant decrease in MAP among the (D group) 66.5 and 4.56 millimeters of mercury as compared to (M group) 73.11 and 4.74 millimeters of mercury (p=0.039) (14) .…”
Section: Discussionmentioning
confidence: 76%
“…Compared to the control group, Bayoumy et al (14) found that the (D group) experienced a statistically significant decrease in HR after anesthetic induction, and at 15, 30, 60, 90, and 120 minutes intraoperatively and postoperatively; at the end of surgery; after extubation; and 30 minutes later if they were given a second dose of ketamine (M group).…”
Section: Discussionmentioning
confidence: 99%
“…The first limitation was the lack of previous studies in this field of the present study. Second, we did not assess the surgical field because our target mean arterial blood pressure was 55–65 mmHg, which has been approved in many previous clinical trials to produce a clear surgical field [ 16 , 28 , 29 ]. Therefore, further studies are warranted.…”
Section: Discussionmentioning
confidence: 99%